Operative techniques in gynecologic surgery - Hatch, Kenneth D. (Operative techniques in gynecologic surgery, 2019)
"The Operative Techniques in Gynecologic Surgery series will put step-by-step surgical techniques at the fingertips of the gynecologic surgeon"--Provided by publisher